Initial Treatment of Venous Thromboembolism - Kearon, Clive (Thrombosis and Haemostasis, 1999)
Goals of the initial treatment of venous thromboembolism (VTE) include the relief of symptoms and stabilization of the patient’s acute medical condition; reversal of vascular occlusion; and the prevention of recurrent VTE, including thrombus extension. The level of priority attached to achieving each of these goals depends on the severity of the patient’s presentation. For most episodes of VTE, all three goals are adequately achieved with anticoagulant therapy alone, which prevents progression of thrombosis while the patient’s endogenous fibrinolytic system gradually reverses vascular obstruction and collateral vessels develop. In a minority of patients, usually those with massive pulmonary embolism (PE) or absolute contraindications to anticoagulant therapy, additional pharmacological or mechanical measures are required to resuscitate the patient, accelerate the reversal of thrombotic occlusion, and/or prevent emboli from reaching the lungs. Anticoagulant therapy, therefore, remains the mainstay of treatment of VTE.The initial phase of anticoagulation with heparin or its derivatives serves two functions. First, it prevents recurrent VTE during the days that oral anticoagulation is being established. As the risk of recurrent VTE is highest acutely, a rapid onset of anticoagulation is a high priority.1-3 Second, this therapy functions to effectively “turn off” thrombosis acutely. Lack of, or inadequate, initial heparin therapy reduces the efficacy of the subsequent maintenance of anticoagulation with vitamin K antagonists.4-6After providing a historical perspective, current approaches to the initial treatment of VTE will be reviewed, concentrating on recent developments and unresolved issues.